Resonance nonlinear reflection from neutron star and additional radiation components of crab pulsar - Kontorovich, V.M.; Spevak, I.S.; Gavrikov, V.K. (Вопросы атомной науки и техники, 2018)
Additional high-frequency components of the pulsar radiation in Crab Nebula are considered as a result of the resonance with the surface electromagnetic wave at nonlinear reflection from of the neutron star surface. This stimulated scattering consists in generation of the surface periodic relief by the incident field and diffraction of the radiation of relativistic positrons on the relief which fly from magnetosphere to the star in the accelerating electric field of the polar gap. Додаткові високочастотні компоненти випромінювання пульсара в Крабоподібній туманності розглядаються як результат резонансу з поверхневою електромагнітною хвилею при нелінійному відбитті від поверхні нейтронної зірки. Це − вимушене розсіювання, яке складається в генерації падаючим полем періодичного рельєфу поверхні і дифракції на ньому випромінювання релятивістських позитронів, що летять з магнітосфери до зірки в електричному полі полярного зазору, яке їх прискорює. Дополнительные высокочастотные компоненты излучения пульсара в Крабовидной туманности рассматриваются как результат резонанса с поверхностной электромагнитной волной при нелинейном отражении от поверхности нейтронной звезды. Это − вынужденное рассеяние, которое состоит в генерации падающим полем периодического рельефа поверхности и дифракции на нём излучения релятивистских позитронов, летящих из магнитосферы к звезде в ускоряющем электрическом поле полярного зазора.